2020
DOI: 10.1097/tp.0000000000002899
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Hypertension and Thrombocytopenia Associated With Intracranial Hemorrhage After Liver Transplantation

Abstract: Background. Intracranial hemorrhage (ICH) is a devastating complication. Although hypertension and thrombocytopenia are well-known risk factors for ICH in the general population, their roles in ICH after liver transplantation (LT) have not been well established. Methods. We performed a retrospective study and hypothesized that intraoperative hypertension and thrombocytopenia were associated with posttransplant ICH. New onset of spontaneous hemorrhage in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…19 The dose of TPA used in a previous report, 20 mg total, was much higher than in our patients, and was thought to contribute to that patient's degree of neurologic injury. Although the incidence of ICH in our patients who received TPA for ICT was higher (27.3%) compared to the reported incidence in all LT (approximately 2%), 20 all ICH self-resolved, no patients died of ICH or required surgery for ICH, and no patients had residual neurologic deficits.…”
Section: Discussioncontrasting
confidence: 74%
“…19 The dose of TPA used in a previous report, 20 mg total, was much higher than in our patients, and was thought to contribute to that patient's degree of neurologic injury. Although the incidence of ICH in our patients who received TPA for ICT was higher (27.3%) compared to the reported incidence in all LT (approximately 2%), 20 all ICH self-resolved, no patients died of ICH or required surgery for ICH, and no patients had residual neurologic deficits.…”
Section: Discussioncontrasting
confidence: 74%
“…Some studies, such as the study conducted by Gao et al . 35 , have suggested that intraoperative hypertension increases mortality in certain types of surgery, whereas others, such as that of Shimada et al . 36 , have demonstrated that intraoperative hypertension may not be associated with myocardial injury and mortality.…”
Section: Discussionmentioning
confidence: 98%
“…The literature search provided insight into the incidence and risk stratification of ICH in patients after LT. The clinical characteristics of the patients, possible risk factors, and the relationship between arterial blood pressure and postoperative ICH in LT recipients were evaluated in three retrospective cohort studies that enrolled a total of 2506 patients [14][15][16]. These studies report consistent evidence on the incidence of postoperative ICH during the observational period, which ranged between 30 days to 12 months, with figures ranging from 2% to 6.5%.…”
Section: Intracranial Hemorrhagementioning
confidence: 98%
“…Similarly, an increased intraoperative mean arterial pressure (MAP) ≥105 mmHg for 10 min or longer, a greater increase in pre-to posttransplant systolic blood pressure, a lower pretransplant serum fibrinogen level, and a higher pretransplant serum bilirubin level were associated with higher incidences of posttransplant ICH (Table 2) [14,15]. Patients with confirmed ICH had higher Model for End-Stage Liver Disease (MELD) scores and were more likely to have preoperative encephalopathy, be on vasopressors, be respirator-dependent, and have hemodialysis [14,15]. LT recipients seronegative for Epstein-Barr virus before LT had higher PCNSL incidence than seropositive recipients.…”
Section: Intracranial Hemorrhagementioning
confidence: 98%